„Jestem ładna, czegoż mi trzeba więcej?” Dandysowski projekt Marii Baszkircew - Poznańska, Justyna (Postscriptum Polonistyczne, 2020)
This article presents an analysis of Maria Baszkircew’s dandyish project on the basis of her Diary (1858–1884). Diagnoses were made mainly in the context of Parnassianism as referred to in Wilde’s idea of life imitating art. The methodologicalinterpretative substructure is Goffman’s concept of selfpresentation and Lacanian psychoanalysis. The purpose of these considerations was to present the essence of Baszkircew’s dandyism, and to prove that her aesthetic life project was closely connected with conditioning, which was dictated by her culture and customs. It concludes that her dandyism was a form of fighting for her own identity, liberty and selfdetermination.